PARAMETERIZATION OF SURFACE MOMENTUM FLUX DURING CONVECTIVE CONDITIONS - Edi Santoso (BPPT, 2000)
Parameterization of surface momentum flux estimates near-surface turbulent momentum fluxes from differences of mean wind speeds between the surface skin and the mid-mixed layer (ML). The rate of this turbulent transport is proportional to the product of a convective velocity times an empirical transport coefficient. To further investigate parameterization of surface momentum flux, some topics are discussed. New data from three different sites within Boundary Layer Experiment - 1996 (BLX96) are presented, and used to evaluate surface momentum flux parameterization. Old data from three other field programs (BLX83, Koorin, and TOGA-COARE) are re-analyzed to test this parameterization. Evidence from virtually all of these experiments indicates that the empirical transport coefficients for momentum fluxes depend on surface roughness.Fluks momentum turbulen dekat permukaan dapat diestimasi dari selisih antara kecepatan angin di batas permukaan (surface skin) dan di bagian tengah lapisan tercampur (mid-mixed layer). Kecepatan dari transpor turbulen ini sebanding dengan perkalian antara koefisien empiris transpor dengan kecepatan konvektif. Untuk pengamatan lebih lanjut akan didiskusikan beberapa hal. Data baru dari hasil pengukuran BLX96 pada 3 lokasi yang berbeda akan digunakan untuk mengevaluasi parameterisasi ini. Sementara data yang diperoleh dari yang pernah dilakukan sebelumnya (BLX83, Koorin, and TOGA-COARE) digunakan untuk menguji hasil parameterisasi ini. Hasil yang diperoleh mengindikasikan bahwa koefisien empiris transpor untuk fluks momentum tergantung pada kekasaran permukaan (surface roughness).